A Consideration of How the Communicative Approach Can Be Used to Teach Grammar to the Third Year Students at Military Technical Academy - Trang, Nguyen Thi Ngoc (VNU Journal of Science: Education Research, 2016)
Abstract: This study aims at considering how Communicative Language Teaching (CLT) can be applied to raise the quality of grammar teaching and learning at Military Technical Academy (MTA). To achieve the objective, two instruments were employed: survey questionnaire and classroom observation. The findings indicate that both teachers and students are quite positive about grammar teaching and learning, but there is still a big gap between the teachers’ limited use of communicative techniques and the students’ need of communicative activities. Based on the observation analysis of a communicative grammar lesson, the researcher came to the conclusion that the “weak” version of CLT may be applied to teach grammar effectively.The study also presents pedagogical implications for applying CLT to teaching grammar in non-English major universities. Keywords : Communicative language teaching, grammar, non-English major universities.